Nanoencapsulation Of The Flavonoids Isolated From Phaleria Macrocarpa Leaf By Casein Micelle - MUHAMAD SAHLAN,; INDRIANTI PRAMADEWI, (International Journal of Pharma and Bio Sciences, 2012)
Phaleria macrocarpa [Scheff.] Boerl. (PM) is known as “Mahkota Dewa”, which originates from Papua Island, Indonesia and grows in tropical areas. It is potential in treating diabetic, cancer and diuretic patients. Methanol extract with further fractionated by ethyl acetate (EAF) of PM leaf have anti-hyperglycemic activity. Flavonoids, the major compounds in the EAF, suggested responsible for this reported activity. Here, we encapsulate the flavonoids by casein micelle (CM) with a homogenizer followed by sonication. The sample was separated by ultra-filtration system and created nano-particles. Encapsulations capacity of the CM was about one milligram flavonoids per a gram CM. Size of particles was analyzed by particle size analysis (PSA) showed that the average size of particles was 109 nm. The results showed that CM to be potential nano-vehicle for the PM leaf extract.